Public Policy and Media Organizations - "Berry, David; Kamau, Caroline" (Surrey, 2013)
Public policy thinking and implementation is both a process of intellectual thought and rationale for governing. This book examines public policy and the influence news media organizations have in the production and implementation of public policy. Part I assesses the impact of political philosophy on public policy thinking and further discusses the meaning of public policy in social democratic systems. It uses the riots that occurred across England in the summer of 2011 as a case-study to focus on how the idea of the $1 (BBig Society$1 (Bwas regenerated by government and used as a basis for public policy thinking. Finally, it investigates how media organizations form news representations of public policy issues that seek to contextualize and reshape policy manufactured for public consumption. Part II provides a psychological exploration of the processes which explain the connection between the media, the public and policy-makers. Does the $1 (Bcommon good$1 (Breally drive public policy-making, or can group processes better explain what policy-makers decide? This second part of the book explores how media workers$1 (Bprofessional identities and practices shape their decisions about how to represent policy news. It also shows how the public identities and corporate interests of media organizations shape their role as referees of public policy-making and how all this culminates in faulty decision-making about how to represent policy news, polarization in public opinion about particular policies, and shifts in policy-makers$1 (Bdecisions.s
Keywords: Policy sciences